1999
DOI: 10.1016/s0893-133x(98)00099-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Novel Antipsychotic Aripiprazole (OPC-14597) with Dopamine and Serotonin Receptor Subtypes

Abstract: cells; C-6 cells; SchizophreniaSchizophrenia is a chronic psychiatric illness with two major types of symptoms-positive or psychotic symptoms, such as hallucinations and delusions, and negative or deficit symptoms, such as amotivation, apathy, and asociality. Approximately 1% of the population suffers from schizophrenia (Kaplan and Sadock 1988). The serendipitous discovery of chlorpromazine four decades ago not only provided the first efficacious therapeutic intervention, but also opened horizons into research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
298
5
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 375 publications
(320 citation statements)
references
References 69 publications
11
298
5
4
Order By: Relevance
“…Thus, when rat D 2 -receptors were expressed in HEK293 cells using an assay buffer containing NaCl (50 mM Tris-HCl, pH ¼ 7.4, 50 mM NaCl, 5 mM MgCl 2 , 0.5 mM EDTA) affinities were 6.8-fold lower than that reported in rat striatal membranes, but a striking 62-fold lower than those values obtained using stably transfected CHO cells assayed in a Na-free buffer (Lawler et al, 1999). The large effect of sodium ions on the measured affinity of aripiprazole is likely due to the fact that sodium ions decrease agonist affinities for D 2 -family receptors (Neve, 1991;Neve et al, 1991Neve et al, , 2001.…”
Section: Affinities Of Aripiprazole For Dopamine Serotonin and Othementioning
confidence: 59%
See 4 more Smart Citations
“…Thus, when rat D 2 -receptors were expressed in HEK293 cells using an assay buffer containing NaCl (50 mM Tris-HCl, pH ¼ 7.4, 50 mM NaCl, 5 mM MgCl 2 , 0.5 mM EDTA) affinities were 6.8-fold lower than that reported in rat striatal membranes, but a striking 62-fold lower than those values obtained using stably transfected CHO cells assayed in a Na-free buffer (Lawler et al, 1999). The large effect of sodium ions on the measured affinity of aripiprazole is likely due to the fact that sodium ions decrease agonist affinities for D 2 -family receptors (Neve, 1991;Neve et al, 1991Neve et al, , 2001.…”
Section: Affinities Of Aripiprazole For Dopamine Serotonin and Othementioning
confidence: 59%
“…Some prior studies have suggested that aripiprazole is a partial agonist at D 2 receptors (Burris et al, 2002), while others have proposed that the drug is 'functionally selective' at D 2 receptors (Lawler et al, 1999). The present experiments thus tested aripiprazole in several different systems, including many not previously studied.…”
Section: Functional Effects At Dopamine Receptorsmentioning
confidence: 94%
See 3 more Smart Citations